Big vessel, massive liner alliances : upsizing, are they working ? Looking from “Cultural” prospective for ocean alliance - Xue, Guorong (2016)
There has been a long history of shipping lines working together to address the issue of strong competition and ensure survival. From the 1870’s Liner Conference to today’s Alliance, collaboration between liner companies has evolved over many different forms due to the changing business environment, however what does not change is the ultimate aim of ensuring individual competitiveness and survivability. So does such form of collaboration, in particular Alliance helps the liner companies to stay competitive and profitable in today’s tough business environment? Based on the past research, it has shown that financial and operation aspect of the alliance has been well researched, however there is a lack of research on how cultural elements could impact the alliance to achieve its intended purposes, and Culture can be simply defined as two or more entities with a set of shared rules. Based on the result obtain through interviews and surveys with industry professionals, the paper examines the relationship between alliance and cultural factors in the liner shipping industry and attempts to use descriptive statistics as well as verification of the past literatures to describe the relationship between performance and cultural factors in liner alliance. The finding suggests that subjective cultures are inversely proportion to objective cultures, in particular subjective cultures such as corporate cultures and political considerations are rather insignificant to alliance success, especially when economic factors such as fleet size complementary and vessel utilisation to achieve low per unit cost are being regard as the most important considerations. Nevertheless, with those finding the paper hope to raise the awareness of the liner companies on how establishing a common Alliance Culture helps to improve their success and survivability in the time of needs.